When push comes to shove ; Blame it on the rain ; Celeste [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Interview with Ramos and General Villa on bombings and the threat of another copu. When will the problem on flooding be resolved. An interview with Celeste Legaspi about her goals, image and philosophy.